2015
DOI: 10.1103/physreve.92.053101
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive force due to magnetohydrodynamic fluctuations in sheared rotating turbulence

Abstract: This article presents a calculation of the mean electromotive force arising from general small-scale magnetohydrodynamical turbulence, within the framework of the second-order correlation approximation. With the goal of improving understanding of the accretion disk dynamo, effects arising through small-scale magnetic fluctuations, velocity gradients, density and turbulence stratification, and rotation, are included. The primary result, which supplements numerical findings, is that an off-diagonal turbulent res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Likewise, a magnetic contribution to the Ω × J effect (Rädler 1969) was found by Squire & Bhattacharjee (2015b) to play a role. Their results were supported with analytical calculations using quasilinear theory (Squire & Bhattacharjee 2015a). However, it is not clear what the implications are for the large R m and fluid Reynolds number R e (along with Strouhal number ∼ 1) regime relevant for galaxies.…”
Section: Introductionmentioning
confidence: 88%
“…Likewise, a magnetic contribution to the Ω × J effect (Rädler 1969) was found by Squire & Bhattacharjee (2015b) to play a role. Their results were supported with analytical calculations using quasilinear theory (Squire & Bhattacharjee 2015a). However, it is not clear what the implications are for the large R m and fluid Reynolds number R e (along with Strouhal number ∼ 1) regime relevant for galaxies.…”
Section: Introductionmentioning
confidence: 88%
“…Ensemble plasma averaging is also implied by any hydrodynamic modelling of plasma phenomena, and recent examples of such modelling were reported by Araki (2015), Bhattacharjee et al. (2015), Stawarz & Pouquet (2015), Squire & Bhattacharjee (2015), Andrés & Sahraoui (2017) and Viciconte, Gréa & Godeferd (2018). Implicitly, plasma ensemble substitutions are present in many numerical plasma simulations (see, e.g.…”
Section: Introductionmentioning
confidence: 94%
“…At this point, things become tricky. Indeed, FOSA calculations (Krause & Rädler 1980; Moffatt & Proctor 1982) show that the Rädler effect alone can promote a dynamo ( ) when the rotation is anticyclonic (corresponding to positive with our convention), but not the shear-current effect ( , Rädler & Stepanov 2006; Rüdiger & Kitchatinov 2006; Sridhar & Subramanian 2009; Sridhar & Singh 2010; Squire & Bhattacharjee 2015 a ). Calculations based on the MTA closure agree with FOSA calculations as far as the Rädler effect is concerned, but find dynamo growth ( ) for the shear-current effect (Rogachevskii & Kleeorin 2003, 2004)!…”
Section: Fundamentals Of Large-scale Dynamo Theorymentioning
confidence: 99%
“…To understand how the Rädler and shear-current effects may affect large-scale dynamos in rotating shear flows, let us have a look at the mean-field dynamo problem for small-scale homogeneous turbulence forced isotropically and non-helically in the simplest possible unstratified, rotating shearing sheet configuration, , , for which and the only non-zero components of the deformation tensor are . Under these assumptions, there are no mean and effects and the kinematic evolution equations for the and components of a -dependent mean magnetic field (defined as the average over and of the total magnetic field) can be cast in the simple form where we have introduced a contracted generalised anisotropic turbulent diffusion tensor appropriate to the configuration of the problem, namely Using (4.8)–(4.10), it can be shown that where is the usual isotropic turbulent diffusion coefficient, is an anisotropic contribution to the tensor arising from the presence of the large-scale strain associated with the shear flow, and , and are contributions to the mean-field tensor arising (similarly to and ) from the presence of rotation, large-scale vorticity, and strain associated with the shear flow (for a detailed derivation, see Rädler & Stepanov 2006; Squire & Bhattacharjee 2015 a ).…”
Section: Fundamentals Of Large-scale Dynamo Theorymentioning
confidence: 99%
See 1 more Smart Citation